2012
DOI: 10.2147/ijn.s32711
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biocompatibility of calcined mesoporous silica particles and fetal blood cells

Abstract: Background:The biocompatibility of two forms of calcined mesoporous silica particles, labeled as MCM41-cal and SBA15-cal, with fetal blood mononuclear cells was assessed in vitro. Methods and results: Fetal mononuclear cells were isolated from umbilical cord blood and exposed to 0.5 mg/mL of MCM41-cal or SBA15-cal for several hours. Transmission electron micrographs confirmed the presence of particles in the cytosol of macrophages, neutrophils, and lymphocytes without noticeable damage to the cellular organell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…As measured by the MTT method, 24 h of exposure gave an IC50 value of 0.15 mg/mL for both the functionalised materials, and this value lowered to 0.09 mg/mL and 0.11 mg/mL after the 48-hour treatment, for carvacrol-and thymol-silica, respectively. In a previous work, Fuentes et al, 2021 determined the cytotoxic effect of bare MCM-41 silica microparticles on HepG2 cells by the MTT assay and confirmed the biocompatibility reported for calcined mesoporous silica (Aburawi et al, 2012;Al-Salam et al, 2011;Samri et al, 2012;Shamsi et al, 2010). Exposing cells to bare MCM-41 silica for 24 h and 48 h led to IC50 values of 18.90 mg/mL and 15.82 mg/mL, respectively (Fuentes et al, 2021).…”
Section: Discussionsupporting
confidence: 57%
“…As measured by the MTT method, 24 h of exposure gave an IC50 value of 0.15 mg/mL for both the functionalised materials, and this value lowered to 0.09 mg/mL and 0.11 mg/mL after the 48-hour treatment, for carvacrol-and thymol-silica, respectively. In a previous work, Fuentes et al, 2021 determined the cytotoxic effect of bare MCM-41 silica microparticles on HepG2 cells by the MTT assay and confirmed the biocompatibility reported for calcined mesoporous silica (Aburawi et al, 2012;Al-Salam et al, 2011;Samri et al, 2012;Shamsi et al, 2010). Exposing cells to bare MCM-41 silica for 24 h and 48 h led to IC50 values of 18.90 mg/mL and 15.82 mg/mL, respectively (Fuentes et al, 2021).…”
Section: Discussionsupporting
confidence: 57%
“…Since we used non-coated SiNP without the addition of any surfactant, potential unspecific effects caused by foreign ions and/or surface functionalizations should be negligible. In addition, signaling processes are likely to be triggered by the generation of reactive oxygen species (ROS) mediated by the cleavage of strained siloxane rings [74][75][76][77]. We showed that aSiNPs accumulate in the cells with increasing particle concentrations correlating with morphological changes and augmented cell toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…The most commonly observed effects of aSiNP exposure include the induction of apoptosis through DNA damage or mitochondria-, TNF-α-, and NO-related signaling pathways [72,73]. Mechanistically, silanol groups (Si-OH) on the nanoparticle surface can interact electrostatically with the cell membrane [74]. Furthermore, their nucleophilic character can attack electrophilic carbonyl groups of proteins [75].…”
Section: Discussionmentioning
confidence: 99%